2011
DOI: 10.1103/physrevb.84.125316
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the electrical properties of Ge/GaAs by film deposition rate and preparation of fully compensated Ge films

Abstract: We investigate the electronic, optical, and structural properties of thin Ge/GaAs(100) films for a variety of growth rates. All of the films have a granular, single-crystal structure, but the electronic properties vary dramatically, with resistivity and carrier concentration changing by more than three orders of magnitude. For high deposition rates, the films are heavily doped and of n-type, with relatively high carrier concentration and low resistivity. The temperature dependence of the resistivity indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, a number of results which deviated from the VRH predictions remain in existence. In addition, the growth conditions [11], impurity doping [12] and crystallization states [13,14] of germanium films also impact their electrical properties. Therefore, it is necessary to carry out more experimental and theoretical research on the electron transport of germanium films.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of results which deviated from the VRH predictions remain in existence. In addition, the growth conditions [11], impurity doping [12] and crystallization states [13,14] of germanium films also impact their electrical properties. Therefore, it is necessary to carry out more experimental and theoretical research on the electron transport of germanium films.…”
Section: Introductionmentioning
confidence: 99%
“…The high deposition rates produce films that are n-type doped with low resistivity (10 -2 cm) and high carrier concentration (410 18 cm 3 ). The temperature dependence of conductivity in these films is very weak and of non-activation [10]. In this work we present a structural study of thermally deposited Ge/GaAs films by transmission electron microscopy (TEM) and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the deposition rate on the properties of thin Ge films on GaAs has not been investigated thoroughly; in most of the reports rather high film deposition rates have been chosen as a rule. Recently we have demonstrated that by varying the deposition rate of Ge/GaAs one can control the transport properties effectively [10]. The high deposition rates produce films that are n-type doped with low resistivity (10 -2 cm) and high carrier concentration (410 18 cm 3 ).…”
Section: Introductionmentioning
confidence: 99%